Patient-derived scaffolds uncover breast cancer promoting properties of the microenvironment. (March 2020) - Landberg, Göran; Fitzpatrick, Paul; Isakson, Pauline; Jonasson, Emma; Karlsson, Joakim; Larsson, Erik; Svanström, Andreas; Rafnsdottir, Svanheidur; Persson, Emma; Gustafsson, Anna; Andersson, Daniel; Rosendahl, Jennifer; et al.
Abstract: Tumor cells interact with the microenvironment that specifically supports and promotes tumor development. Key components in the tumor environment have been linked to various aggressive cancer features and can further influence the presence of subpopulations of cancer cells with specific functions, including cancer stem cells and migratory cells. To model and further understand the influence of specific microenvironments we have developed an experimental platform using cell-free patient-derived scaffolds (PDSs) from primary breast cancers infiltrated with standardized breast cancer cell lines. This PDS culture system induced a series of orchestrated changes in differentiation, epithelial-mesenchymal transition, stemness and proliferation of the cancer cell population, where an increased cancer stem cell pool was confirmed using functional assays. Furthermore, global gene expression profiling showed that PDS cultures were similar to xenograft cultures. Mass spectrometry analyses of cell-free PDSs identified subgroups based on their protein composition that were linked to clinical properties, including tumor grade. Finally, we observed that an induction of epithelial-mesenchymal transition-related genes in cancer cells growing on the PDSs were significantly associated with clinical disease recurrences in breast cancer patients. Patient-derived scaffolds thus mimics in vivo -like growth conditions and uncovers unique information about the malignancy-inducing properties of tumor microenvironment. Highlights: Patient-derived scaffolds (PDSs) from breast cancer mimics in vivo conditions. Structure, protein composition and induced gene expression are PDS-specific. PDS proteins mediate stromal effects in breast cancer. PDSs can uncover malignancy-inducing properties of a cancer microenvironment. PDSs can potentially be used in cancer drug design and screening.